Organizational Citizenship Behavior and Career Outcomes - Bergeron, Diane M.; Shipp, Abbie J.; Rosen, Benson; Furst, Stacie A. (Journal of Management, 2013)
Existing research suggests that relationships among organizational citizenship behavior (OCB), task performance, and individual career outcomes are necessarily positive. The authors question this assumption and hypothesize that in organizations with outcome-based control systems, time spent on OCB comes at a cost to task performance. Building on this idea, the authors propose not only that time spent on task performance is more important than time spent on OCB in determining career outcomes (i.e., performance evaluation, salary increase, advancement speed, promotion) in an outcome-based control system but also that time spent on OCB may negatively impact career outcomes. Results based on archival data from 3,680 employees in a professional services firm lend some support for these ideas. Specifically, time spent on task performance was more important than OCB in determining all four career outcomes. Further, controlling for time spent on task performance, employees who spent more time on OCB had lower salary increases and advanced more slowly than employees who spent less time on OCB. These findings suggest that relationships between OCB and outcomes are more complex than originally thought and that boundary conditions may apply to conclusions drawn about the outcomes of OCB.